2023
DOI: 10.1021/acsami.3c00052
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Elimination of Reactive Oxygen Species and Activation of Nrf2 by Ultrasmall Nanoparticles to Relieve Acute Kidney Injury

Abstract: Excess reactive oxygen species (ROS) can induce serious acute kidney injury (AKI) to result in numerous deaths annually in clinical practice. Elimination of excess ROS by advanced nanotechnology is a very promising AKI therapy. In this Article, we report that PVP-stabilized and quercetin-functionalized ultrasmall Cu2–x Se nanoparticles (abbreviated as CSPQ NPs) can efficiently scavenge ROS and increase the expression of intracellular antioxidative enzymes by activating the nuclear factor erythroid 2-related fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, the harm caused was lessened when the AKI mice were treated with CSPB NPs. Tubular damage scores were calculated by the previously reported method, [54] which shows that the overall kidney tissue damage was reduced after the AKI mice were treated with CSPB NPs (Figure 4d).…”
Section: Treatment and Immune Response Of Mice Bearing Iri-induced Ak...mentioning
confidence: 94%
“…However, the harm caused was lessened when the AKI mice were treated with CSPB NPs. Tubular damage scores were calculated by the previously reported method, [54] which shows that the overall kidney tissue damage was reduced after the AKI mice were treated with CSPB NPs (Figure 4d).…”
Section: Treatment and Immune Response Of Mice Bearing Iri-induced Ak...mentioning
confidence: 94%
“…41–43 In their study, Bao et al synthesized and analyzed polyvinylpyrrolidone (PVP)-stabilized and quercetin-functionalized ultrasmall Cu 2− x Se nanoparticles that demonstrated the ability to mitigate glycerol-induced AKI and enhance renal function by effectively scavenging ROS and upregulating the Nrf2 protein. 44 In addition, Casanova et al reported the development of a micellar formulation of quercetin, which exhibited enhanced bioavailability and water solubility compared to free quercetin, and demonstrated promising therapeutic efficacy in the treatment of cisplatin-induced AKI. 45 However, the treatment of AKI through the development of new quercetin-functionalized nanozymes that possess antioxidant and anti-inflammatory properties still holds promising potential.…”
Section: Introductionmentioning
confidence: 99%
“…When the production of ROS surpasses the cellular antioxidant defense mechanisms, it triggers the oxidation of various cellular components, such as DNA, lipids, and proteins. This oxidation can damage the cellular matrix, resulting in oxidative stress, ultimately leading to cellular damage [ 2 , 3 ]. Research indicates a close correlation between the impairment of renal tubular epithelial cells and the early pathological changes associated with kidney stone formation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%